Genetically engineered mesenchymal stem cells using viral vectors: a new frontier in anti-angiogenic therapy - Choy, Ewa Yee Wa; Choy, Ker Woon; Woon, Kai Siong; Muhammad Aidil Wafi; Then, Kong Yong; Then, Khong Lek (Penerbit Universiti Kebangsaan Malaysia, 2024)
Mesenchymal stem cells (MSCs) are adult stem cells that possess the remarkable ability to self-renew and differentiate into various cell lineages. Due to their regenerative potential, MSCs have emerged as the most commonly used stem cell type in clinical applications. Angiogenesis, the formation of new blood vessels, plays a critical role in several pathological conditions, including ocular neovascular diseases, cancer, and inflammatory disorders. Conventional anti-angiogenic therapies face limitations such as frequent visits for repeated doses, off-target effects and resistance development. Recent advances in genetic engineering techniques have opened up novel avenues in regenerative medicine. Genetically engineering MSCs using viral vectors presents a promising strategy to specifically target angiogenesis and enhance anti-angiogenic therapies’ efficacy. Viral vectors, including lentiviruses, adeno-associated viruses and adenoviruses, provide an effective means of delivering therapeutic genes into MSCs, allowing the expression of a wide range of therapeutic agents, including anti-angiogenic proteins. This review explores the frontier of using genetically engineered MSCs delivered through viral vectors as a potent anti-angiogenic therapeutic approach. By leveraging the unique properties of MSCs and the targeted delivery capabilities of viral vectors, this approach initiates the potential to revolutionize anti-angiogenic therapy, offering new possibilities for the treatment of angiogenesis-related diseases.